Teaching of Classical Chinese Prose under Bilingual Environment in Singapore - Jia, Li (Sinología hispánica. China Studies Review, 2019)
The teaching of classical Chinese prose in Singapore involves challenges peculiar to the bilingual environment, which suggest a need for new strategies based on a crucial recognition of the difference between teaching literature and teaching language. The paper argues for a key pedagogical approach based on the teaching of literary aspects in ancient prose with the help of problem-based learning. This would also involve systematic classification in order to consolidate different strategies suited for different types of Classical Chinese Prose. These strategies include mind mapping, five thinking hats and so on. Through an approach of problem-based learning, one may motivate students to explore ancient articles more enthusiastically, foster their critical thinking and creative ability, thereby enhancing cognitive ability, and increasing their interest in learning ancient articles. Through the reading, understanding and analysis of subtle words, one may improve on students’ ability in literary appreciation, and prompt them to explore more sophisticated interpretation, thereby enhancing their cultivation in the humanities.